Teologi Pesantren dalam Konteks Tradisi Keberagamaan NU (Studi Kasus Pondok Pesantren Kyai Syarifuddin Lumajang): Pesantren Theology in the Context of NU Religious Tradition (Case Study of Kyai Syarifuddin Islamic Boarding School, Lumajang) - Muniron Muniron (Fenomena, 2015)
The existence of Islamic Theology, a discipline of Islamic studies focusing on God or Islamic creed, holds a significant position in Islamic boarding schools (pesantren) as the oldest Islamic educational institutions in Indonesia. Considering that pesantren, to a certain extent, can be regarded as the base of Nahdlatul Ulama (NU), the existence of both is intriguing to study, especially concerning the theological system adhered to in pesantren within the context of NU's religious tradition. This research stems from the focus: how is pesantren theology in the context of NU's religious tradition (Case Study of Syarifuddin Islamic Boarding School, Lumajang)? It is then narrowed down to two aspects: (1) What are the doctrinal aspects of the theology of Syarifuddin Islamic Boarding School in Lumajang? (2) How are the doctrinal aspects of the theology of Syarifuddin Islamic Boarding School in the context of NU's religious tradition or model? The research objectives are formulated as follows: (1) to describe the doctrinal aspects of the theology of Syarifuddin Islamic Boarding School in Lumajang; and (2) to describe the doctrinal aspects of the theology of Syarifuddin Islamic Boarding School in the context of NU's religious tradition. To achieve these objectives, a qualitative case study approach was employed, with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the interactive model analysis technique by Miles and Huberman, and data validity was tested through source and method triangulation. After analyzing the collected data, the research conclusions are as follows. (1) The doctrinal aspects of pesantren theology are represented in its views on God's attributes, the concept of human actions, ru’yatullah (seeing God in the afterlife), and the concept of faith. God possesses attributes, and these attributes are neither His essence nor separate from His essence; all human actions, good and bad, are created by Allah, although there is an ineffective human contribution; God can be seen with the naked eye by believers in the afterlife; the essential element of faith is believing in the heart everything conveyed by the Prophet Muhammad (PBUH). (2) The theology of Syarifuddin Islamic Boarding School, viewed from its doctrinal aspects, aligns with and follows the Ahl as-Sunnah wa al-Jama’ah school, particularly the Ahl as-Sunnah Khalafiah Asy’ariyah, in line with NU's religious tradition or model. Keberadaan Teologi Islam, sebuah disiplin ilmu keislaman yang fokus bahasannya tentang Tuhan atau akidah Islam, menempati posisi penting di pondok pesantren dalam posisinya sebagai lembaga pendidikan Islam tertua di Indonesia. Dan mengingat pondok pesantren dalam batas tertentu bisa dikatakan basis Nahdlatul Ulama’ (NU) maka keberadaan keduanya menarik untuk dikaji, terutama menyangkut sistem teologi yang dipegangi di pesantren dalam konteks tradisi keberagamaan NU. Penelitian ini bertolak dari fokus penelitian: bagaimana teologi pesantren dalam konteks tradisi keberagamaan NU (Studi Kasus Pesantren Syarifuddin Lumajang)? Dan kemudian difokuskan pada dua hal berikut: (1) Bagaimana aspek doktrinal teologi pesantren Syarifuddin Lumajang? (2) Bagaimana aspek doktrinal teologi pesantren Syarifuddin Lumajang dalam konteks tradisi atau model keberagamaan NU? Adapun rumusan tujuan penelitian ini adalah: (1) mendeskripsikan aspek doktrinal teologi pesantren Syarifuddin Lumajang; dan (2) mendeskripsikan aspek doktrinal teologi pesantren Syarifuddin Lumajang dalam konteks tradisi keberagamaan NU. Untuk mencapai tujuan penelitian yang telah ditetapkan tersebut, dipergunakan pendekatan penelitian kualitatif jenis studi kasus, dengan teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Analisis data dengan menggunakan teknik analisis model interaktif Miles dan Huberman, dan uji keabsahan data menggunakan triangulasi sumber dan triangulasi metode. Setelah dilakukan analisis terhadap data yang telah terhimpun, akhirnya dihasilkan simpulan penelitian sebagai berikut ini. (1) Aspek doktrinal teologi pesantren terepresentasikan dalam pandangannya mengenai sifat Tuhan, konsep perbuatan (manusia), ru’yatullah, dan konsep iman. Tuhan memiliki sifat dan sifat itu bukan dzat Tuhan dan bukan pula lain dari dzat-Nya; semua perbuatan yang muncul dari manusia, baik dan buruk, diciptakan oleh Allah meski ada kontribusi manusia yang bersifat tidak efektif; Tuhan di akhirat bisa dilihat dengan mata kepala oleh orang beriman; unsur esensial iman adalah meyakini dengan hati segala yang disampaikan oleh Nabi Muhammad saw. (2) Teologi pesantren Syarifuddin dilihat dari aspek doktrinalnya adalah sejalan dan mengikuti madzhab Ahl as-Sunnah wa al-Jama’ah khususnya Ahl as-Sunnah Khalafiah Asy’ariyah sebagaimana tradisi atau model keberagamaan NU.